(untitled) (Contemporary Journal of Social Science Review, 2025)
This research investigates the impact of project-based learning (PBL) on developing students’ creativity, critical thinking, and problem-solving skills across educational levels. Through a mixed-methods approach combining quantitative assessments and qualitative observations, this study examined how structured PBL interventions affect cognitive development and skill acquisition compared to traditional instructional methods. Data collected from 247 students across multiple educational institutions revealed significant improvements in creative thinking flexibility, critical reasoning depth, and complex problem-solving capabilities among PBL participants. Notably, students in PBL environments demonstrated enhanced ability to transfer knowledge across domains, generate multiple solution pathways, and engage in deeper metacognitive processes. The findings suggest that contextually-rich, student-directed learning experiences foster the development of higher-order thinking skills essential for 21st-century success. This research provides evidence-based insights for educators and policymakers seeking to implement effective PBL strategies to cultivate students’ cognitive abilities and prepare them for future academic and professional challenges in an increasingly complex world.